THE STUDY OF THE RUBAS FORTIFICATION IN 2018 - Gmyra, Ludmila Borisovna; Saidov, Vadim Artemovic; Magomedov, Usup Abdusalamovic (History, Archeology and Ethnography of the Caucasus, 2019)
The article presents the material of the excavation of the monumental fortification of the middle of the VI century on the river Rubas (Rubas fortification), conducted in 2018. Studies of the monument, accidentally discovered in 2014, have been carried out since 2016. In 2016–2017 two military engineering objects were identified - a monumental defensive wall and an arched structure. The defensive complex on the river Rubas has an intricate structure and layout. The full length of the main wall, oriented in the South – West direction, has not yet been established. Following the excavations of 2016–2017, its 20th segment had a continuation both to the north and to the south - in the direction of the riverbed Rubas. The functional purpose of the wall embedded in the trunk wall in the direction East – West is not defined either. There is no data on the appointment of another wall, attached to the construction of an arched structure from the north. The research in 2018 revealed new sections of the main defensive wall, the total length of which was 28 m. The wall has a continuation both to the north and to the south. New data on the technology of its facilities were received. In the northern segment, a layer-by-layer alternation of crushed stone and masonry from large stone blocks was found in the interwall space. The stone blocks of the eastern facade and backfilling had pairwise narrow slits for the installation of metal brackets that held the masonry together, which strengthened the structure. New sections of the wall oriented in the direction of East – West were also revealed, and it was established that it continues to the east (it is possible that this is another main wall directed to the coast of the sea). The archaeo- and paleoseismological surveys of 2018 revealed significant deformations of the military engineering structures of the Rubas fortification, caused by a powerful earthquake. The strongest flooding followed by mudflows were the reason for the destruction of this fortification object approximately in the X century.